Affecting factors on the performance of online marketing in the tourism industry (The Peerian Journal, 2024)
Despite the increasing growth of affiliate marketing in Iraq, especially in the tourism industry, researchers have not paid much attention to this field. The purpose of this research was to investigate the effective factors on measuring the performance of online marketing in the country's tourism industry. Considering that this research was a descriptive survey in terms of its development goal and in terms of the method of gathering information, first a set of criteria for measuring the performance of affiliate marketing were identified with review studies. After interviewing the tourism marketing experts, the questionnaire was distributed among the statistical sample, i.e. the tourism activists of the country. After collecting the questionnaire, data analysis, extraction and ranking of appropriate criteria were done to measure the performance of online marketing in the country's tourism industry. The results of this research showed that the six factors of display capabilities, communication capabilities, financial factors, creation of competitive advantage, attraction capabilities and brand creation are important factors for measuring the performance of affiliate marketing in the country's tourism industry.